Interpretive description: a viable methodological approach for nursing research - Ilara Parente Pinheiro Teodoro; Vitória de Cássia Félix Rebouças; Sally Elizabeth Thorne; Naanda Kaana Matos de Souza; Lídia Samantha Alves de Brito; Ana Maria Parente Garcia Alencar (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To present a theoretical reflection about the origin and the assumptions of the "Interpretive Description" method, and to discuss its applicability in Nursing and Health research. Method: Theoretical-reflective study, based on articles and books published by proponent of this approach, as well as scientific articles in which the authors reported having used this method in their studies. Results: It was evidenced that the "Interpretive Description" arose from the need to generate a better understanding of clinical practices in Nursing. This approach has its roots in the methodological traditions of the Social Sciences, although it differs from them in terms of its excessive rigidity and essentially theoretical objectives. The proposed method has been applied in several studies either in Nursing as other areas of Health. Conclusion: The "Interpretive Description" is considered a feasible approach for the production of knowledge in Applied Sciences such as Nursing.